Analisis Determinan Ketimpangan Wilayah di Provinsi Daerah Istimewa Yogyakarta (DIY) Tahun 2013-2020 - Nizar Fahmi; Nugroho Sumarjiyanto Benedictus Maria (Diponegoro Journal of Economics, 2023)
This study aims to analyze the classification of economic development, development inequality, and the effects of economic growth, the open unemployment rate, and the Human Development Index (HDI) on development inequality in the DIY Province from 2013 to 2019. The approach used in this research is quantitative, utilizing secondary data obtained from Badan Pusat Statistik for the years 2013 to 2019. The method employed to analyze the classification of economic growth is Klassen typology. The Williamson Index is used to analyze development inequality, while panel data regression is applied to examine the factors influencing development inequality. Based on the results of the research on the classification of economic development, it is evident that areas with advanced and fast development are Yogyakarta and Sleman, while fast-developing areas include Kulonprogo, and relatively underdeveloped areas are Gunungkidul and Bantul. The results of the Williamson Index indicate that the largest development inequality exists in the Kulonprogo, Bantul, and Gunungkidul areas, suggesting that there is inequality in community access to development outcomes. Furthermore, the results of the panel data regression show that the economic growth variable has an insignificant negative effect on development inequality, the unemployment variable has a significant positive effect on development inequality, and the HDI variable has a significant negative effect on development inequality in DIY Province. To reduce development inequality in DIY Province, it is necessary to increase employment opportunities based on regional potential and improve human resources to achieve inclusive economic growth.